UPAYA MENINGKATKAN HASIL BELAJAR MATERI REPRODUKSI SEL MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SMA - Asminah, Siti (Universitas Tanjungpura, 2021)
In biology subjects, biology material is considered difficult because the material is abstract and cannot be observed directly by students. In the syllabus, the basic competence for cell reproduction is to explain the relationship between the meiotic mitotic division process with indicators to identify the characteristics, stages of mitosis and meiosis and to differentiate the processes and theirfunctions. So it is necessary to observe activities through pictures. Based on the results of observations, in general, students like biology subjects with a percentage of >75%. From the results of these observations, it is known that 53.82% of the total students in class XII IPA did not reach the KKM (Minimum Passing Grade Criteria) for genetic material and cell reproduction. This still shows that more than 90% of students have not met the KKM of 80. For this reason, classroom action research (CAR) is needed to conduct. One of the learning models that can improve the achievement of students’ learning achievement is the PBL learning model because it can develop thinking skills,encouraging students to collaborate in solving problems to find solutions to the problems they face. By applying the PBL learning model in biology learning on cell reproduction material, it was found that in the first cycle there were 42.10% of students who scored below the minimum passing grade criteria (KKM > 80) who got an average score of 74.66. In the second cycle there was an increasein students’ learning achievement who got below the KKM only 10.52% of the total number of students, and students who scored above the KKM were 89.48% with the average score of all students was 82.72% . From the results of this study, it was concluded that the PBL learning model had a positive impact on improving the biology learning achievement of class XII IPA2 students on cellreproduction.